New concept of the container terminal in the port of Rijeka - Dundović, Čedomir (Array, 2007)
The port of Rijeka is a port of national interest open to national and international public traffic. It is mostly intended for the movement of goods with the container traffic playing an important role. As laid down in the Port Classification and Physical Plan of the Primorskogoranska County, Rijeka is a port of a special international economic importance for the Republic of Croatia. The largest part of the Croatian imports and exports of goods is realized through the port of Rijeka which is also a major transit port in Croatia for the goods from Hungary, Slovakia, the Czech Republic, Austria, Italy and Serbia. The essential factors of the port of Rijeka geotraffic position are the physical characteristics of its location and its connection with the hinterland. The construction of the new leveled rail line from Zagreb to Rijeka, the reconstruction of the Rijeka-Zagreb motorway to a full profile highway, the canalization of the river Sava from Šamac to Sisak and the construction of the Vukovar – Šamac Canal will make Rijeka an important seaport for the flows of goods from the Danube basin to the Adriatic. In the future period, the structure of the goods flow will be marked by the growth of the container traffic which has, by today, reached the upper limit of the container terminal storage and handling capacity. If the port of Rijeka wishes to maintain its competitive ability in the North Adriatic ports catchment area, it should meet such increased transport needs by adequate expansion and new investments to bemade in a short-time period. This paper aims at focusing particularly on the container terminal Brajdica and its expansion possibilities which, contrary to other projects requiring a longer period of time for their realization and for bringing corresponding traffic solutions, include specific space and traffic predispositions